Standard specification for electrodeposited coatings of lead and lead-tin alloys on steel and ferrous alloys
This specification covers the requirements for electrodeposited coatings of lead and lead-tin alloys on steel and ferrous alloys. The coatings of lead-tin alloys are those that range in tin content up to but not exceeding 15 mass %. The coatings ranging between 3 and 15 mass % in tin content are known also as "terne" metallic electrodeposits. This specification does not apply to sheet, strip, or wire in the unfabricated form.